ANALISIS PENGEMBANGAN SISTEM PENYEDIAAN AIR BERSIH DESA SAOJO KABUPATEN POSO PROVINSI SULAWESI TENGAH - Alventus Joyvel Fogel Berg Gente; Jeffrey Delarue; Titof Tulaka (Sustainable Construction (SUSCON), 2024)
Water is a very important need in human life. In all activities carried out by humans, they definitely need water, especially clean water. This research aims to realize the development of a clean water supply system that is able to serve water needs for the next 10 years. The study location is in Saojo Village. This research uses data collection techniques including primary data and secondary data. The results of the research show that there are 2 sources of raw water or clean water that are used to meet the water needs of the people of Saojo Village, source 1 can produce a water discharge of 8.13 liters/second and water source 2 produces a water discharge of 3.61 liters/second, by Therefore, the clean water distribution area is separated into zone 1 and zone 2. The division of 2 clean water service zones is an effective solution so that the water sources in each zone can be distributed according to the clean water needs of the community in the clean water service area zone 1 and zone 2 .